Review of the genus Acanthophorella Antić & Makarov, 2016 (Diplopoda, Chordeumatida, Anthroleucosomatidae), with descriptions of three new species from the Caucasus - Antić, Dragan; Šević, Mirko; Barjadze, Shalva; Makarov, Slobodan (European Journal of Taxonomy, 2023)
The present paper is devoted to the description of three new species of the genus Acanthophorella Antić & Makarov, 2016 from Georgia, western Caucasus: A. devi Antić sp. nov. and A. valerii Antić sp. nov., both presumed troglobionts and each from a single cave, and the epigean A. aurita Antić sp. nov. The troglobiotic Acanthophorella barjadzei Antić & Makarov, 2016 is reported from two additional caves, with further descriptive notes given. Notes on the ecology and localities, and a distribution map for all six species of the genus are presented. A key is given to all members of the Flagellophorella complex. The relationships within the complex and the distribution and troglomorphism in the genus Acanthophorella are briefly discussed.